Investigating the Moisture Susceptibility Resistance of Asphalt Mixes Modified with Silica Fume Additive (Journal of Engineering, 2025)
Moisture induced damage is a prevalent pavement distress commonly observed by road agencies. The damage caused by moisture significantly affects the pavement's lifespan and performance. This research investigated the influence of silica fume (SF) on the susceptibility to moisture. Three concentrations of silica fume were used 3%, 6%, and 9% by weight of the binder. A thermal camera has been used to detect variations in homogeneity in the modified asphalt during the mixing process. The optimal asphalt content was 4.92, 5.02, 5.16, and 5.22 for the control and modified mixtures. The moisture susceptibility was evaluated by measuring the tensile strength ratio (TSR) and index of retained strength (IRS). The thermal images showed that the silica fume particles in the mixture were uniformly distributed, as indicated by the convergence of colors at 160°C. The findings showed that the inclusion of SF at 6% decreased sensitivity to moisture, corresponding to an increase in TSR and IRS of 12.49% and 13%, respectively.